The sunny side - Milne, A. A. (Alan Alexander), 1882-1956 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Sunny Side" by A. A. Milne is a collection of humorous essays and short stories written in the early 20th century. The work reflects the spirit of British society during the 1920s and offers a whimsical take on everyday experiences and the interactions of its characters. Throughout this collection, Milne employs witty observations and light-hearted anecdotes to explore themes of human nature, social customs, and the quirks of friendship. The opening of "The Sunny Side" sets the stage for a narrative infused with playful banter among a group of friends, particularly focusing on a character named Simpson who has planned a gathering to discuss a significant yet amusing suggestion. As anticipation builds regarding the nature of his proposal, the friends indulge in whimsical speculation about what it could mean, alternating between excitement and skepticism. Their interactions are rooted in camaraderie, underscored by Milne's trademark humor as they navigate social dynamics and the humorous absurdities of their lives. This opening immediately immerses the reader into the charming world of Milne's characters, promising a lighthearted exploration of their adventures together. (This is an automatically generated summary.)
Oranges and lemons -- Men of letters -- Summer days -- Wartime -- Home notes -- A few guests -- And others.
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Sunny_Side
Release date is 2004-09-12
Produced by Rick Niles and John Hagerson, Mary Meehan and the Online Distributed Proofreading Team
Keywords: Short stories, English; English essays -- 20th century